2019
DOI: 10.12740/pp/onlinefirst/99971
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the expression of BAX, BCL2, BIRC6, CASP3, CASP9 apoptosis genes during the first episode of schizophrenia

Abstract: Cel pracyCelem pracy było 1) porównanie poziomu ekspresji genów apoptozy BAX, BCL2, BIRC6, CASP3, CASP9 u pacjentów ze schizofrenią i w grupie kontrolnej oraz 2) określenie powiązań pomiędzy poziomem ekspresji genów a parametrami morfologicznymi krwi obwodowej oraz nasileniem objawów psychopatologicznych.MetodaDo badania włączono 21 pacjentów z rozpoznaniem schizofrenii wg ICD-10 oraz 26 zdrowych osób. Oceniano ekspresję genów w limfocytach krwi obwodowej, parametry laboratoryjne oraz nasilenie objawów psychop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Two genes, apoptotic chromatin condensation inducer 1 (ACIN1) and programmed cell death 10 (PDCD10), are involved in apoptosis. Our finding that hypomethylation of cg23712970 in ACIN1 and PDCD10 may result in increased expression of these genes is partially consistent with the recent finding that expression levels of the BCL2 and CASP3 apoptosis genes were significantly higher in the peripheral blood lymphocytes of schizophrenic patients [ 44 ]. Analysis of mRNA expression in the post-mortem brain tissue of patients with SZ also revealed altered mRNA expression in the IFITM2, TIAL1, PDCD6, and MCL genes, which are involved in programmed cell death [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…Two genes, apoptotic chromatin condensation inducer 1 (ACIN1) and programmed cell death 10 (PDCD10), are involved in apoptosis. Our finding that hypomethylation of cg23712970 in ACIN1 and PDCD10 may result in increased expression of these genes is partially consistent with the recent finding that expression levels of the BCL2 and CASP3 apoptosis genes were significantly higher in the peripheral blood lymphocytes of schizophrenic patients [ 44 ]. Analysis of mRNA expression in the post-mortem brain tissue of patients with SZ also revealed altered mRNA expression in the IFITM2, TIAL1, PDCD6, and MCL genes, which are involved in programmed cell death [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, we observed alterations in the expression of genes involved in apoptotic pathways [ 57 ]. The consistent findings in the literature [ 58 ], supported by our group, suggesting that dysregulation of apoptotic mechanisms underlies the molecular basis of SZ, led us to propose anti-apoptotic molecules as a challenging prodromal therapeutic option to halt onset and/or SZ progression.…”
Section: Introductionsupporting
confidence: 76%
“…In doing so, dexamethasone inhibits solid tumour and haematologic malignant cell growth, while also suppressing mitogen‐induced proliferation of a wide range of other cell types (Park et al., 2013). Caspase‐3 promotes apoptosis and caspase‐9 plays a signalling and initiation role (Hakem et al., 1998), while Bcl‐2 modulates mitochondrial integrity, functioning as an anti‐apoptotic (Szymona et al., 2019). The present study found that DEXA administration increased caspase‐3 and caspase‐9 expression and decreased immunoreactivity to Bcl‐2 in rats’ testicular tissue.…”
Section: Discussionmentioning
confidence: 99%